Less is more: the best test for anastomotic leaks in rectal cancer patients prior to ileostomy reversal - Lindner, Simon; Eitelbuss, Steffen; Hetjens, Svetlana; Gawlitza, Joshua Felix Michael; Hardt, Julia; Seyfried, Steffen; Galata, Christian; Reißfelder, Christoph; Şandra-Petrescu, Flavius Ionuţ; Herrle, Florian (International journal of colorectal disease, 2021)
No clear consensus exists on how to routinely assess the integrity of the colorectal anastomosis prior to ileostomy reversal. The objective of this study was to evaluate the accuracy of contrast enema, endoscopic procedures, and digital rectal examination in rectal cancer patients in this setting.
Gesehen am 20.04.2023